PARTISIPASI MASYARAKAT PENGUNJUNG DALAM MENJAGA KEBERSIHAN LINGKUNGAN DI LOKASI WISATA DANAU SIPOGAS KABUPATEN ROKAN HULU - Gustika Fitriani; Nurhamlin " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2020)
Lake Sipogas tourism object is an object established in 1987 at first Lake Sipogas was only a dam where the water was diverted to the rice fields of local residents and fulfilled the need for clean water for residents. Starting to be visited by visitors in 1988 until now. This is 1) to find out the characteristics of Lake Sipogas tourist attraction, 2) to find out visitors’ participation in maintaining the cleanliness of Lake Sipogas attraction in a study using an incidental technique and the authir found 6 people as informants writers 2 men and 4 women. This type of research uses qualitative descriptive. Findings in this study that the author can find out the characteristics of visitors and participation by visitors of the environment of Lake Sipogas tourist attraction. The result of the study are the visitors’ efforts to maintain the cleanliness pf the environment in the Lake Sipogas tourist attraction locations and wal nor are all visitors who have the same participation between visitors. Keywords : Participation, Lake Sipogas, Environmental Cleanliness.